1989
DOI: 10.1111/j.1476-5381.1989.tb11933.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a dihydropyridine‐sensitive and conotoxin‐insensitive release of noradrenaline and uptake of calcium in adrenal chromaffin cells

Abstract: These results show that in these neurone-like cells, release may be effected by calcium influx through DHP-sensitive but co-conotoxin-insensitive VSCC, a result inconsistent with the suggestion that w-conotoxin blocks both L-type and N-type neuronal calcium channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 27 publications
1
33
1
Order By: Relevance
“…L-type channels predominate the secretion despite their contribution to the total current in single cell experiments is partial or very small, as in the case of BCCs [73,74]. A dominance of L-type channel-mediated secretion is thus reported in bovine [4,[75][76][77], mouse [78,79], rat [9,10,80,81] and cat chromaffin cells [82,83] more or less independently of whether intact adrenal glands or cultured chromaffin cells are used. The reason for this general finding is that during prolonged depolarization (far from physiological conditions) L-type channels are probably more favored because of their slower time-dependent inactivation and lower steady-state inactivation with respect to the other HVA channels (P/Q, N and R), which inactivate more rapidly and completely during prolonged stimuli.…”
Section: L-type Channels and Fast Exocytosis In Chromaffin Cellsmentioning
confidence: 80%
“…L-type channels predominate the secretion despite their contribution to the total current in single cell experiments is partial or very small, as in the case of BCCs [73,74]. A dominance of L-type channel-mediated secretion is thus reported in bovine [4,[75][76][77], mouse [78,79], rat [9,10,80,81] and cat chromaffin cells [82,83] more or less independently of whether intact adrenal glands or cultured chromaffin cells are used. The reason for this general finding is that during prolonged depolarization (far from physiological conditions) L-type channels are probably more favored because of their slower time-dependent inactivation and lower steady-state inactivation with respect to the other HVA channels (P/Q, N and R), which inactivate more rapidly and completely during prolonged stimuli.…”
Section: L-type Channels and Fast Exocytosis In Chromaffin Cellsmentioning
confidence: 80%
“…In analogy to chromaffin cells, the N-channel in PC12 cells is not functional (shown in Fig, 1A). Chromaffin cells contain oCgTx binding sites [29,30] and w-CgTx-sensitive currents 131,321 but neither catecholamine secretion nor increase of [Ca2']i transients were antagonized by w-CgTx [33,34]. Fu~he~ore, synaptota~in, a small synaptic vesicleassociated protein which is involved in mediating transmitter release [35], is absolutely non-essential in the secretion process in PC12 cells [36].…”
Section: The L-type Ca2' Channel Expressed In Pc12 Cellsmentioning
confidence: 99%
“…The latter can also be blocked by v-agatoxin IVA at concentrations above 10 Ž . nM Wheeler et al, 1994 Owen et al, 1989;Rosario et al, 1989 . Indeed, while several groups including ours have consistently emphasized the lack of effect of v-conotoxin GVIA 2q Ž in depolarization-evoked Ca influx this paper and Ballesta et al, 1989;Owen et al, 1989;Rosario et al, .…”
mentioning
confidence: 99%
“…nM Wheeler et al, 1994 Owen et al, 1989;Rosario et al, 1989 . Indeed, while several groups including ours have consistently emphasized the lack of effect of v-conotoxin GVIA 2q Ž in depolarization-evoked Ca influx this paper and Ballesta et al, 1989;Owen et al, 1989;Rosario et al, . 1989;Duarte et al, 1993a , others-using single cell w 2q x Ca measurements-have reported the occurrence of i cell-specific and variable inhibitory effects of the toxin Ž .…”
mentioning
confidence: 99%